Mapping health-related quality of life after kidney transplantation by group comparisons: a systematic review. Issue 12 (2nd August 2021) - Wang, Yiman; Hemmelder, Marc H; Bos, Willem Jan W; Snoep, Jaapjan D; de Vries, Aiko P J; Dekker, Friedo W; Meuleman, Yvette
Abstract: Background: Health-related quality of life (HRQOL) is becoming an increasingly important outcome in kidney transplantation (KT). To describe HRQOL in kidney transplant recipients (KTRs), this systematic review summarizes literature that compared HRQOL among KTRs and other relevant populations [i.e. patients receiving dialysis, patients on the waiting list (WL) for KT, patients with chronic kidney disease (CKD) not receiving renal replacement therapy (RRT), the general population (GP) and healthy controls (HCs)] and themselves before KT. Methods: The literature search was conducted in PubMed, Embase, Web of Science and the Cochrane Library. Eligible studies published between January 2000 and October 2020 were included. Results: Forty-four studies comprising 6929 KTRs were included in this systematic review. Despite the study heterogeneity, KTRs reported a higher HRQOL after KT compared with pre-transplantation and compared with patients receiving dialysis with or without being on the WL, especially in disease-specific domains (i.e. burden and effects of kidney disease). Additionally, KTRs had similar to marginally higher HRQOL compared with patients with CKD Stages 3–5 not receiving RRT. When compared with HCs or the GP, KTRs reported similar HRQOL in the first 1 or 2 years after KT and lower physical HRQOL and lower to comparable mental HRQOL in studies with longer post-transplant time. Conclusions: The available evidence suggests that HRQOL improves after KT and can be restored to but not always maintained at pre-CKD HRQOL levels. Future studies investigating intervention targets to improve or maintain post-transplant HRQOL are needed.